Inflammatory factors collaboratively link Helicobacter pylori-induced gastritis to gastric cancer - Zhang, Mingze; Su, Ade; Song, Houji; Zhang, Siyu; Deng, Yuan; Jing, Wutang; Guo, Jin; Zhan, Weipeng; Ma, Yuntao; Hu, Ming (Frontiers in Immunology, 2025)
Long-term inflammatory reaction may promote gastric cancer initiation and development through multiple mechanisms. Recent studies have demonstrated that inflammatory mediators play a crucial role in the transition from gastritis to gastric cancer. Pro-inflammatory cytokines, chemokines, and other signaling molecules interact and synergistically regulate gastric epithelial cell proliferation, apoptosis, migration, and invasiveness, thereby promoting tumorigenesis. Specifically, interleukins activate immune cells, induce the secretion of inflammatory mediators, and maintain local immune responses; however, in the context of cancer, they exhibit a dual role by both enhancing anti-tumor immunity and driving tumor progression. Tumor necrosis factor amplifies immune responses by stimulating the production of pro-inflammatory cytokines, yet excessive or chronic Tumor necrosis factor activity is a hallmark of autoimmune diseases. Interferons initiate antiviral responses, modulate immune cell functions, and influence the inflammatory cascade. Chemokines primarily mediate the recruitment of immune cells to sites of infection, inflammation, or injury, but also play key roles in immune evasion and tumor immune regulation. This review summarizes the cooperative roles of these inflammatory mediators in the progression from gastritis to gastric cancer and discusses their potential as therapeutic targets. A better understanding of these mechanisms may facilitate the development of novel strategies for the prevention and treatment of gastric cancer.